Evaluation of Caspase-1, Interleukin-1β, and Interleukin-18, in the Middle Ear Effusion in Children With Otitis Media With Effusion - Shanshan Liu (Frontiers Media S.A., 2021)
Objectives: The present study aimed to assess the expression of caspase-1 and caspase-1-dependent processing of cytokines, such as interleukin (IL)-1β and IL-18, in the middle ear effusion of children with otitis media with effusion (OME) in order to identify the potential role of inflammasomes in OME.Methods: This study included 29 children scheduled for myringotomy with the insertion of tympanostomy tubes due to OME. Middle ear effusion (MEE) was collected during the surgery. Caspase-1, IL-1β, and IL-18 were assayed using enzyme-linked immunosorbent assay kits. The levels were compared between those with mucoid and serous MEE and those with and without a history of ventilation tube insertion.Results: Caspase-1, IL-1β, and IL-18 were detected in all samples. The caspase-1, IL-1β, and IL-18 levels did not significantly differ between mucoid samples and serous samples. No statistical significances were discovered in caspase-1, IL-1β, and IL-18 levels between with and without a history of ventilation tube groups. There was a significant negative correlation between IL-1β and IL-18 and the duration of OME (p < 0.05). However, no significant correlation was found between caspase-1 and disease duration.Conclusions: Inflammasomes may participate in the inflammatory process of OME. IL-1β and IL-18 levels in the MEE decreased over time.